2021
DOI: 10.1002/mabi.202100092
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of Alleviating Tumor Hypoxia and Enhancing Tumor Therapeutic Effect by Macromolecular Nanomaterials

Abstract: Hypoxia as one of the most prominent features in tumors, has presented negative effects on tumor therapies including photodynamic therapy, radiotherapy, and chemotherapies, leading to the tumor regeneration and metastasis. Recently, nanomedicines have been proposed to handle the hypoxia dilemma. Some nanomedicines alleviated hypoxia to enhance the therapeutic effect, others used hypoxia‐sensitive substances to treat tumor. Among them, macromolecular nanomaterials‐based nanomedicine has attracted increased rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 93 publications
0
14
0
Order By: Relevance
“…PFCs demonstrated an outstanding oxygen affinity due to their fluorine atoms in the carbon skeleton ( 21 ). Of the high biocompatibility and chemical stability, PFCs have been widely used in the clinic, such as in organ transplantation and ultrasound imaging.…”
Section: Physical Strategiesmentioning
confidence: 99%
“…PFCs demonstrated an outstanding oxygen affinity due to their fluorine atoms in the carbon skeleton ( 21 ). Of the high biocompatibility and chemical stability, PFCs have been widely used in the clinic, such as in organ transplantation and ultrasound imaging.…”
Section: Physical Strategiesmentioning
confidence: 99%
“…Methods suggested to restore the tumor oxygen supply before or during radiotherapy include erythrocyte transfusion, erythropoietin administration, and hyperbaric oxygen (HBO) treatment, among others. To date, compelling evidence has demonstrated that hypoxia can be successfully overcome with the use of relevant nanomaterials, as also summarized by several excellent reviews[ 241 - 243 ]. For instance, some simulated oxygen- or water-soluble components can be employed to improve the effect of radiotherapy.…”
Section: Application Of Nanotechnology In Conquering Therapeutic Resi...mentioning
confidence: 99%
“…Glucose oxidase (GOD) is a good choice to enhance H 2 O 2 and to lower pH by oxidizing glucose into H 2 O 2 and gluconic acid. , According to the Warburg effect, tumor cells are more dependent on nutrients, such as glucose, than normal cells, and glucose plays a key role in promoting the metabolism of tumor cells. ,, Therefore, GOD-mediated glucose metabolism cannot only accelerate Fenton/Fenton-like reactions but also the starvation of tumors for starvation therapy. , However, one of the necessary conditions for GOD to oxidize glucose is O 2 , and the concentration of O 2 in most solid tumor tissues is noticeably lower than that in normal tissues. , Unfortunately, O 2 depletion caused by GOD can further exacerbate the hypoxic microenvironment . A convenient and effective strategy to overcome hypoxia has recently been introduced by generating O 2 in situ instead of transporting it, where high H 2 O 2 levels in the TME can self-produce O 2 by loading enzymes, inorganic nanocomposites, or metal oxides. For instance, catalase-mimicking platinum nanoparticles (Pt NPs) have been widely used in the construction of nanomaterials as a low-cost alternative to natural enzymes, which can decrease tumor hypoxia by catalyzing H 2 O 2 production of O 2 in situ. , Of special note is that sufficient H 2 O 2 can be generated during the oxidation of glucose by GOD to promote Fenton-like reactions .…”
Section: Introductionmentioning
confidence: 99%